Risk Factors for Surgical Treatment of Lumbar Degenerative Disc Disease in Middle‐aged and Older Women: A Prospective Case–Control Study of 2370 Subjects - Zhang, Yuchen; Yuan, Suomao; Chen, Xing; Zhang, Zhaoqing; Yang, Xiaorong; Wang, Shuo; Tian, Yonghao; Wang, Lianlei; Liu, Xinyu (Orthopaedic surgery, 2024)
Objective Given the distinct physiological and societal traits between women and men, we propose that there are distinct risk factors for lumbar degenerative disc disease surgeries, including lumbar disc herniation (LDH) and lumbar spinal stenosis (LSS), in middle‐aged and older populations. However, few studies have focused on middle‐aged and older women. This study aims to identify these risk factors specifically in this population. Methods In this case–control study, the study group comprised 1202 women aged ≥ 45 years who underwent operative treatment of lumbar degenerative disc disease (LDH, n = 825; LSS, n = 377), and the control group comprised 1168 women without lumbar disease who visited a health examination clinic during the same period. The study factors included demographics (age, body mass index [BMI], smoking, labor intensity, and genetic history), female‐specific factors (menopausal status, number of deliveries, cesarean section, and simple hysterectomy), surgical history (number of abdominal surgeries, hip joint surgery, knee joint surgery, and thyroidectomy), and systemic diseases (hypercholesterolemia, hypertriglyceridemia, hyper‐low‐density lipoprotein cholesterolemia, hypertension, diabetes, cardiovascular disease, and cerebrovascular disease). Multivariate binary logistic regression analysis was used to calculate the odds ratio (OR) and 95% confidence interval (95% CI) of associated factors. Results The risk factors for surgical treatment of LDH in middle‐aged and older women included BMI (OR = 1.603), labor intensity (OR = 1.189), genetic history (OR = 2.212), number of deliveries (OR = 1.736), simple hysterectomy (OR = 2.511), hypertriglyceridemia (OR = 1.932), and hyper‐low‐density lipoprotein cholesterolemia (OR = 2.662). For surgical treatment of LSS, the risk factors were age (OR = 1.889), BMI (OR = 1.671), genetic history (OR = 2.134), number of deliveries (OR = 2.962), simple hysterectomy (OR = 1.968), knee joint surgery (OR = 2.527), hypertriglyceridemia (OR = 1.476), hyper‐low‐density lipoprotein cholesterolemia (OR = 2.413), and diabetes (OR = 1.643). Cerebrovascular disease was a protective factor against surgery for LDH (OR = 0.267). Conclusions BMI, genetic history, number of deliveries, simple hysterectomy, hypertriglyceridemia, and hyper‐low‐density lipoprotein cholesterolemia were independent risk factors for surgical treatment of both LDH and LSS in middle‐aged and older women. Two disparities were found: labor intensity was a risk factor for LDH patients, and knee joint surgery and diabetes were risk factors for LSS patients. In the four dimensions of demographics, female‐specific factors, surgical history, and systemic diseases, we used multivariate binary logistic regression analysis to explore the risk factors for surgical treatment of lumbar degenerative disc disease in middle‐aged and older women. We found that body mass index, genetic history, number of deliveries, simple hysterectomy, hypertriglyceridemia, and hyper‐low‐density lipoprotein cholesterolemia were common independent risk factors for surgical treatment of lumbar disc herniation (LDH) and lumbar spinal stenosis (LSS)in middle‐aged and older women. Two disparities were found: labor intensity was a risk factor for patients with LDH, and knee joint surgery and diabetes were risk factors for patients with LSS.